Antibacterial Activity of Pseudomonas Aeruginosa ISP1RL3 Against Multidrug Resistance Bacteria - Indraningrat, Anak Agung Gede; Purnami, Pande Putu Christine Putri; Aryastuti, Anak Agung Sri Agung; Wijaya, Made Dharmesti (Postgraduate, University of Mataram, 2023)
Seaweed-associated bacteria have a pivotal role to synthesize arrays of secondary metabolites. This study described a bacterial isolate encoded as ISP1RL3 that was isolated from seaweed Eucheuma cottonii. Ethyl acetate extracts of ISP1RL3 was screened against non-multidrug bacteria (Staphylococcus aureus ATCC 25923, Streptococcus mutans FNCC 0405, Escherichia coli ATCC 25922, Klebsiella pneumoniae ATCC 700603) and multi-drug resistance bacteria (Methicilin-resistance S. aureus (MRSA), E. coli ESBL, K. pneumoniae ESBL, dan A.baumanii ESBL). Our result showed that ISP1RL3 displayed rod structure, Gram negative and identified as Pseudomonas aeruginosa. The crude extract displayed strong antibacterial activity against all bacterial test with the range zone of inhibition of 10 mm – 18 mm. The GC-MS analysis detected the presence of 13 antibacterial compounds with four dominant moleculer were o-Xylene, Ethylbenzene, p-Xylene and Benzene, 1,3-dimethyl. Overall, this finding highlights the potency of seaweed-associated bacteria to synthesize active compounds against multidrug resistance bacteria.